Baking kinetics of muffins in convection and steam assisted hybrid ovens (baking kinetics of muffin...) - Sakin-Yilmazer, Melike; Kemerli, Tansel; Isleroglu, Hilal; Ozdestan, Ozgul; Guven, Gonul; Uren, Ali; Kaymak-Ertekin, Figen (Elsevier Sci Ltd, 2013)
Effects of oven type and baking temperature on acrylamide concentration, surface browning, temperature profiles and drying rates of muffins were investigated. Muffins were baked in convection and steam assisted hybrid ovens at 145, 160 and 175 degrees C for different baking times. For all oven types, the acrylamide concentration of muffins increased with increasing baking time and temperature (p < 0.05). The formation was considered as the first order reaction kinetics except for the lowest baking temperature at natural convection and steam assisted hybrid ovens. The reaction rate constant, k was found to be in the range of 0.027-0.078 (min(-1)). For the forced convection oven, the effect of baking temperature on acrylamide concentration followed the Arrhenius type of equation; with activation energy of 36.35 kJ/mol. The minimum drying rate was observed by the steam assisted hybrid oven, at all conditions. Steam assisted baking resulted in lower acrylamide concentration at all baking temperatures, while providing the average moisture content not significantly different. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Acrylamide; Steam baking; Drying; Hybrid oven; Kinetic modelling